The Clinical handbook of endocrinology and metabolic disease - Robin, Noel I (Parthenon, 1996)
This is a complete textbook on clinical endocrinology and metabolic disease, written by a preeminent teacher, scholar, and physician. In his Introduction, Dr. Robin says, \"I have written this text to provide an integrated compendium of the practice of clinical endocrinology, whereby the infrastructure of physiology and pathophysiology would be meshed with the realities of pragmatic medical practice. I have also tried to make this a review for physicians, residents, and students of all levels and interests. I feel this book can serve a useful and readable purpose in presenting a spectrum of issues and problems in clinical endocrinology and metabolism with appropriate depth, background, relevance, and resolution.\" His book covers all endocrine disorders and metabolic diseases and contains illustrative clinical cases with commentary.
Clinical handbook series
Keywords: metabolické nemoci; endokrinologie; Endocrinology; vnitřní lékařství; Metabolic Diseases